Prevalence and Significance of Non-conventional Antiphospholipid Antibodies in Patients With Clinical APS Criteria - Litvinova, Elena; Darnige, Luc; Kirilovsky, Amos; Burnel, YANN; de Luna, Gonzalo; Dragon-Durey, Marie-Agnes (Frontiers in Immunology, 2018)
Background: The biological diagnostics of APS takes into account the persistent positivity for anticardiolipin and/or anti-β2GP1 antibodies and/or presence of lupus anticoagulant (LA). However, some new non-conventional antiphospholipid antibodies have emerged that could help in the diagnosis of APS. Objectives: To study the potential usefulness of non-conventional antiphospholipid antibodies in clinical practice. Methods: 87 patients, aged from 15 to 92 years were included and classified in following groups: 41 patients. positive for the conventional antibodies with clinical criterion of APS (31 with primary APS and 10 secondary), 17 seronegative APS patients (i.e. persistent negativity for the conventional antibodies with a strong clinical suspicion of APS), 11 asymptomatic antiphospholipid antibodies carriers (i.e. persistent positivity for the conventional antibodies without clinical evidence of APS), and 18 patients presenting with a first thrombotic or obstetrical event). IgG and IgM were detected to the following antigens: phosphatidylserine/prothrombin (PS/PT) by ELISA, and phosphatidic acid, phosphatidyl-ethanolamine, phosphatidyl-glycerol, phosphatidyl-inositol, phosphatidylserine, annexin V, prothrombin, cardiolipin and β2GP1 by immunodot. Anti-2GP1 IgA and anti-2GP1domain I IgG were detected by chemiluminescence. Results:. Positivity for the non-conventional antibodies was correlated with APS severity; patients with CAPS being positive for 10.7 (Median, Range: 5-14) non-conventional antibodies. 9/17 seronegative patients were positive for at least one of non-conventional antibodies. A study of non-supervised hierarchical clustering of all markers revealed that anti-PS/PT antibodies showed high correlation with the presence of LA. All patients with APS triple positivity (highest risk profile) exhibited also persistent positivity for anti-PS/PT antibodies. Conclusions: Our findings suggest that non-conventional APS antibodies could be useful for patients classified as seronegative APS. Furthermore, anti-PS/PT antibodies could be a surrogate APS biological marker of LA to classify in high-risk profile patients treated by direct oral anticoagulants, in whom LA detection cannot be achieved.